2016
DOI: 10.5433/1679-0359.2016v37n2p715
|View full text |Cite
|
Sign up to set email alerts
|

Depth-stratified soil sampling for assessing nematode communities

Abstract: This study assessed the importance of stratified soil sampling on the detection (and therefore the distribution) of nematode communities and the differentiation of ecosystems by collecting stratified soil samples at intervals of 10 cm and non-stratified samples from 0 to 30 cm in two soil management systems (no-tillage and conventional tillage) and in a native forest fragment. The nematode frequency and prominence values were obtained after extraction by successive screening operations, sugar floatation clarif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Within the grave, there was an overall reduction in nematode abundance and richness with depth. Previous studies have reported that approximately 70% of nematodes exist in the top 20 cm of soil and their distributions are associated with available food sources [85,86]. Our findings of elevated abundances at 30‒35 cm, in conjunction with high variation in samples at those depths, is likely due to elevated bacterial and fungal abundances in these areas.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Within the grave, there was an overall reduction in nematode abundance and richness with depth. Previous studies have reported that approximately 70% of nematodes exist in the top 20 cm of soil and their distributions are associated with available food sources [85,86]. Our findings of elevated abundances at 30‒35 cm, in conjunction with high variation in samples at those depths, is likely due to elevated bacterial and fungal abundances in these areas.…”
Section: Discussionsupporting
confidence: 57%
“…With few exceptions [8486], most field studies of nematodes focus on a single depth range, usually within the top 30 cm of the soil profile [38,47,49,52,53,56,87]. Our study compared multiple depths, and revealed that abundance, richness, and diversity decreased with depth both within and outside the grave.…”
Section: Discussionmentioning
confidence: 84%
“…We focused on the upper layers of soil because it has been demonstrated that approximately 70% of nematodes exist in the top 20 cm of soil. Nematode community composition at a local scale is most commonly associated with available food sources, both horizontally and vertically [28,47,48]. Therefore, we hypothesized that the highly enriched interface soils and deeper soils might harbor unique nematode community assemblages and/or successional patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, nematode community diversity and successional patterns have been shown to be sensitive indicators of soil enrichment and disturbance in agricultural systems [31][32][33][34][35][36][37][38][39][40][41][42][43] and composting processes [44,45]. Many field studies of nematodes focus on the upper 30 cm of soil, where the majority of free-living nematodes reside [24,31,[35][36][37][38][39][40][41]43,[46][47][48][49]. Vertical and horizontal distributions of soil nematodes are most commonly driven by food source location [47,48]; nematode density, particularly those of bacterivores, correlates with areas enriched in soil organic carbon (SOC), and therefore higher densities of bacterial biomass [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation